Cross-cultural adaptation, reliability and validity tests of the Chinese version of the Profile Fitness Mapping neck questionnaire - Lu Qi; Rui Chang; Enming Zhang (BMC Musculoskeletal Disorders, 2023)
Abstract Objective To translate and culturally adapt the Profile Fitness Mapping neck questionnaire (ProFitMap-neck) into the Chinese version and evaluate its psychometric properties. Methods The procedure of translation and cross-cultural adaptation was performed according to the recommended guidelines. A total of 220 patients with chronic neck pain (CNP) and 100 individuals without neck pain participated in the study. Internal consistency, test-retest reliability, content validity and construct validity were investigated. Results The Chinese version of ProFitMap-neck (CHN-ProFitMap-neck) showed adequate internal consistency (Cronbach’s α = 0.88–0.95). A good test-retest reliability was proven by the intraclass correlation coefficient (ICC3A,1 = 0.78–0.86). Floor-ceiling effects were absent. Exploratory factor analysis revealed 6 factors for the symptom scale and 4 factors for the function scale. The CHN-ProFitMap-neck showed a moderate to high negative correlation with NDI (r = 0.46–0.60, P < 0.01), a small to moderate negative correlation with VAS (r = 0.29–0.36, P < 0.01), and a small to high positive correlation with SF-36 (r = 0.21–0.52, P < 0.01). No significant correlation between the CHN-ProFitMap-neck function scale and VAS (P > 0.05) or the mental health domain of the SF-36 was found (P > 0.05). The CHN-ProFitMap-neck scores were significantly lower in the CNP group than in the non-CNP group (P < 0.01). Conclusions The CHN-ProFitMap-neck had acceptable psychometric properties and could be used as a reliable and valid instrument in the assessment of patients with chronic neck pain in mainland China.